Reference model of government in information technologies-it for university institutions - Yrigoyen-Quintanilla, Manuel (2016)
Government in information techonologies-IT was developed to help organizations make better and more efficient use of IT, supporting them to achieve their strategic objectives with the participation and full commitment of senior management. The premise of this investigation is that this approach can and should be applied in university institutions; accordingly, an analysis was carried out about the state of the art of this concept and the main reference frameworks and standards to be applied available on the market. As a result of this analysis, an IT Governance model (GTIUP) is proposed, applicable to Peruvian universities as well as two supporting tools for its implementation.